Investigation of muck drawing in blocks with trapezoid sills - Stupnik, Mykola; Kalinichenko, Olena (My University, 2018)
The article is aimed at determining regularities of muck drawing in blocks and developing the technology of enhancing of muck ore parameters through shaping a trapezoid block sill. To confirm the suggested assumptions, study regularities of forming and determine contours of crests after full muck drawing from the second stage blocks, laboratory experiments have been conducted on drawing muck ore on the boundary with solidifying backfill massif of I stage stopes. For the first time there have been determined numerical dependencies of ore losses in crests on the contact with the solidifying backfill massif of the I stage stopes after ore drawing from the II stage blocks on the dead stope height and dips of side surfaces of trapezoid basis of sill pillars when forming the trapezoid sill with inclined side surfaces of the lower part of the I stage stopes. There are developed methods of calculating ore losses in crests on the contact with the solidifying backfill massif of I stage stopes after muck drawing from the II stage blocks. There are proposed methods of determining optimal parameters of mining ore deposits considering minimization of re losses in crests and increase of muck extraction from II stage blocks.